Octreotide ameliorates sepsis-induced pelvic inflammation in female rats by a neutrophil-dependent mechanism - YEGEN, BERRAK; ŞENER, GÖKSEL (ELSEVIER SCIENCE INC, 2005)
Sepsis is a generalized inflammatory response, which involves organ systems remote from the locus of the initial infectious insult, accompanied by the release of cytokines and the subsequent formation of reactive oxygen and nitrogen species. The aim of this study was to investigate the possible protective effect of octreotide (OCT), a synthetic somatostatin analogue, against sepsis-induced oxidative damage in the uterine and ovarian tissues of rats. Sepsis was induced by caecal ligation and puncture method in female Wistar albino rats. Sepsis and sham operated (control) groups received either saline or OCT (50 mug/kg, i.p.; Novartis) immediately after the operation and at 12 h. Twenty-four hours after the surgery, rats were decapitated and serum TNF-alpha levels and tissue malondialdehyde (MDA) content, glutathione (GSH) levels and mycloperoxidase (MPO) activity were determined in the uterus and ovaries. Oxidant-induced tissue fibrosis was determined by tissue collagen contents. while the extent of tissue injuries was analyzed microscopically. Sepsis increased serum TNF-alpha levels and resulted in decreased GSH levels and increased MDA levels, MPO activity and collagen contents in both the uterus and the ovaries (p < 0.05-0.001) indicating the presence of the oxidative damage, as also confirmed by histological analysis. On the other hand, OCT administration reversed these oxidant responses and reduced the severity of microscopic damage (p < 0.001). In conclusion, OCT protects against sepsis-induced oxidative injury of the uterine and ovarian tissues by diminishing neutrophil infiltration, an important source of oxygen free radicals. Our results suggest that OCT may be of therapeutic value in ameliorating sepsis-associated pelvic inflammation. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: sepsis; octreotide; neutrophil; uterine; ovary; ACUTE ABDOMINAL HYPERTENSION; INTESTINAL ISCHEMIA; FREE-RADICALS; INJURY; MANAGEMENT; MELATONIN; SOMATOSTATIN; PERITONITIS; PROTECTION; GLUTATHIONE